Comparative evaluation of CBN wheels with abrasive grains of different friability applied to steel and ductile iron grinding process - Talon, Anthony Gaspar [UNESP]; Souza Rodrigues, Matheus de [UNESP]; Garcia, Mateus Vinicius [UNESP]; Lopes, Jose Claudio [UNESP]; Ribeiro, Fernando Sabino Fonteque; Mello, Hamilton Jose de [UNESP]; Sanchez, Luiz Eduardo De Angelo [UNESP]; Aguiar, Paulo Roberto [UNESP]; Bianchi, Eduardo Carlos [UNESP] (Springer, 2021)
The industrial market demands productivity and highest quality. Abrasion machining is a crucial point for achieving both requirements. In view of this importance, in this work, a comparative analysis is made between two wheels with different friability (low and high) in the cylindrical grinding of SAE 4340 steel and ductile iron SAE D-7003 with three feed rates (0.25, 0, 50, and 1.00 mm/min) under conventional cooling and lubrication conditions. The output parameters were average surface roughness (Ra), roundness error, wheel wear, specific energy, microhardness, and cost analysis. In a complementary way, qualitative analyzes of the surface were performed through optical microscopy, scanning electron microscopy (SEM), and confocal microscopy. It is observed that the greater ductility of the iron causes 18% rougher surfaces and less tool wear. Note that the specific energy is reduced by at least 10% with more friable wheels. On average, roundness errors are 30% lower for SAE 4340 steel, with no microstructural changes for both materials. Finally, the implementation costs for the different grinding wheels decrease with an increase in the rate of advance.
Keywords: Cylindrical grinding; Grinding wheel friability; SAE 4340 steel; SAE D-7003 ductile iron